PENYELESAIAN SENGKETA PERDATA DI LUAR SIDANG PENGADILAN (STUDI KASUS PENGUSAHA CATERING DI KOTA SEMARANG) (Forum Ilmu Sosial, 2008)
The Existence of law in the society is badly needed to keep the orderliness, safety and peace. Besides,law is also used to settle the conflicts within the society. Some conflicts belong to the civil law occursinacontract law, in which there is an agreement inside. The agreement which made by the involved partsof dispute settlement. If there is a dispute, it will be settled trough the court or outside the court. Theproblem of theresearch is stated as follows: what factors which make the people prefer to settles their civildispute outside the court? The problem is divided into: (1) What reasons which make the civil dispute inthe society of Semarang Municipality? (2) What factors which make the settlement of civil dispute doneoutside the court? ; What is the effect of that kind of settlement? The aims of the research are: (1) to knowthe reasons of emerging the civil dispute in Semarang Municipality; (2) to know the factors which makethe people settle their civil dispute outside the court. The result shows that the factor, which influencesthe catering businessmen/women in settling their dispute outside the court, is motivated by cultural andeconomic factors. Based on the result, it is suggested to settle the dispute outside the court firstly, to getthe intended settlement live, all parts involved in the dispute get the satisfaction and also fulfil their needs.Keywords: Settlement of civil dispute, outside the court, catering business